Produktionens skyggespil: De gotiske motiver i den socialistisk-realistiske produktionsroman - Rosenstand, Simon (Passage - Tidsskrift for litteratur og kritik, 2020)
The production novel is widely considered to be the most exemplary socialist-realist genre regarding ideological and narrative conformity. The scholarly reception of the genre has hitherto paid little attention to its many incongruent stylistic features, including its striking Gothic motifs. I argue that they carry both literary and political imports, which are yet to be explored in depth. In this article, I pursue the Gothic motifs in the genre’s first and most exemplary incarnation, Feodor Gladkov’s Cement from 1925.